(untitled) (Journal of Informatics Education and Research, 2024)
In order to examine the intentional attention status of children aged 6 to 9 with minor mental retardation in the Mekong Delta of Vietnam, the study identified four criteria and six tests that measured the physical fitness of these children at low and near-medium levels. As a result, 16 physical activities from two groups were used experimentally in the study. Group 1 focuses on physical fitness, which includes exercises on fundamental motor abilities; Group 2 uses movement games to develop the children’s purposeful attention span and physical fitness. Research on implementing specific physical exercises in accordance with programs for kids aged 6 to 9 who have minor mental retardation was conducted at several Mekong Delta specialty schools for a period of ten months. The findings demonstrate that children with minor mental impairments have improved in their deliberate attention, their capacity to focus their attention, and their attention sustainability. All ages’ physical fitness has increased. But while doing the chosen physical activities, the experimental group fared better in the following tests than the control group did: In alternative assessments, the test group surpassed the control group, exhibiting superior performance in various activities, such as the standing long jump (centimeters), one-legged standing balance (seconds), targeting a ball throw (time), and the seated forward bend posture (centimeters) in a nine-year-old girl.